Relationship between Crude Palm Oil (CPO) Futures prices and Selected Southeast Asia Equity Market-Empirical Evidence - Siaw, Louis Kai Ying (2015)
The relationship between commodities market and equities market has been known to have a negative correlation close to no correlation and generally have no volatility spillover exists between both of the markets. Therefore, there is diversification benefit as while one market is going down, another market is going up to offset the losing position in the down market. Besides that, non-volatility spillover exists between the market will also presents no spillover variance of one market to another variance of the market hence, as mention, portfolio diversification may be achieve. However, such relationship has changes during the financial crisis from year 2008 to the end of year 2010 where high correlation can be seen in the crisis and volatility spillover at the time is statistically significant. After the crisis, the relationship between the markets is seen to be return to normal. Since CPO futures has been traded as a financial securities as mention, the relationship as explained will thus could be applied in the particular market with Southeast Asia equities indices. To conclude, the relationship has to be further analyse to acquire a better understanding of the relationship as it is not as easy as just following the traditional theoretical views.